2018
DOI: 10.29219/fnr.v62.1478
|View full text |Cite
|
Sign up to set email alerts
|

Green tea (Camellia sinensis) aqueous extract alleviates postmenopausal osteoporosis in ovariectomized rats and prevents RANKL-induced osteoclastogenesis in vitro

Abstract: BackgroundGreen tea (Camelliasinensis [L.] Kuntze) belongs to the plant family Theaceae and is mainly distributed in East Asia, the Indian subcontinent and Southeast Asia. This plant has been proven to be beneficial to human health, and green tea is the second most consumed beverage in the world after water. However, until now, the effect of green tea aqueous extract (GTE) upon postmenopausal osteoporosis has remained unclear. In this study, we investigated the therapeutic effects of GTE on estrogen deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“…Increased levels of TRAP and CTX were shown in OVX rats [Solberg et al, 2014]. A previous study showed that tea consumption in rats with OVX-induced bone loss can suppress the level of TRAP, one of the osteoclast-specific genes [Wu et al, 2018]. Investigation of the effect of WT on serum TRAP levels in OVX rats in our study is the first in the literature.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Increased levels of TRAP and CTX were shown in OVX rats [Solberg et al, 2014]. A previous study showed that tea consumption in rats with OVX-induced bone loss can suppress the level of TRAP, one of the osteoclast-specific genes [Wu et al, 2018]. Investigation of the effect of WT on serum TRAP levels in OVX rats in our study is the first in the literature.…”
Section: Introductionsupporting
confidence: 52%
“…Serum TRAP levels increased in the OVX rats with respect to the sham group but significantly decreased in the OVX + WT group. In a previous study, aqueous extract of green tea was shown to suppress RANKL-induced osteoclastogenesis in vitro, reducing TRAP gene expression because of this inhibition [Wu et al, 2018]. Similarly, black tea extracts were reported to reduce serum TRAP levels in the OVX rats [Das et al, 2009].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Green tea extract (25, 50, and 100 µg/mL, 48 h) has shown to inhibit RANKL-induced osteoclast formation in the mouse macrophage-like cell line RAW264.7 related to NFATc1, cathepsin K, C-Fos, and MMP-9 gene levels reduction [103]. Moreover, the isolated compound gallocatechin gallate (oxidation product of epigallocatechin-3-gallate) at 10 µM concentration inhibited osteoclastogenesis more potently than epigallocatechin-3-gallate through gene and protein downregulation (TRAP, c-Src, β3-Integrin, cathepsin K, and MMP-9) and master transcriptional regulators downregulation (NFATc1 and c-Fos) in RAW264.7 cells [104].…”
Section: Camellia Sinensis and Osteoporosismentioning
confidence: 99%
“…Identification of agents that helps bone loss prevention would have substantial effect on the development of treatments for osteoporosis. Earlier studies have proposed the possibility of a nutritional approach as an alternative for the prevention of postmenopausal osteoporosis [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%